The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1096/fasebj.24.1_supplement.104.1
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence against women is associated with lower household food security in rural Bangladesh

Abstract: PurposeThis research was intended to examine whether there is a relationship between household food security and domestic violence among households in rural Bangladesh.MethodsThe study uses data collected from the USAID/FANTA funded 2001–2003 Bangladesh Food Insecurity Measurement and Validation Study conducted by Tufts University. The study measured both physical and psychological abuse of women by their husbands using scales developed from the data. Household food security was measured using the Household Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…3 9-11 Domestic violence is a challenging and complex social issue for women as it has been reported to be strongly linked to the lack of women empowerment. [12][13][14][15][16] Correspondingly, previous studies also indicate that there is a significant relationship between domestic violence and decision-making power. 17 Another crucial indicator that has a detrimental impact on women's empowerment is the degree of household food insecurity, as well as several health issues, including nutrition, child feeding practices, health-seeking behaviour and domestic violence.…”
Section: Open Accessmentioning
confidence: 88%
See 1 more Smart Citation
“…3 9-11 Domestic violence is a challenging and complex social issue for women as it has been reported to be strongly linked to the lack of women empowerment. [12][13][14][15][16] Correspondingly, previous studies also indicate that there is a significant relationship between domestic violence and decision-making power. 17 Another crucial indicator that has a detrimental impact on women's empowerment is the degree of household food insecurity, as well as several health issues, including nutrition, child feeding practices, health-seeking behaviour and domestic violence.…”
Section: Open Accessmentioning
confidence: 88%
“…The literature suggests that many factors which affect a woman’s ability to make their own decisions, including better socioeconomic status (SES), higher education level, older aged women, female household head, degree of household food security status and not experiencing domestic violence 3 9–11. Domestic violence is a challenging and complex social issue for women as it has been reported to be strongly linked to the lack of women empowerment 12–16. Correspondingly, previous studies also indicate that there is a significant relationship between domestic violence and decision-making power 17.…”
Section: Introductionmentioning
confidence: 99%
“…However, we assessed the associations by calculating odds ratios in multinomial logistic regression. Thus, these associations could be symmetric relationships, since many studies have shown that food insecurity status is one predictor of domestic violence and empowerment ( 9 , 28 , 29 ). However, improving these indicators might enhance food security status.…”
Section: Discussionmentioning
confidence: 99%